Effects of raw soybeans, roasted soybeans, and soybean oil on finishing pig performance - Goodband, Robert D.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two trials were conducted to evaluate the effects of raw soybeans, roasted soybeans, and soybean oil on finishing pig performance. In trial 1 pigs were fed a low protein control diet containing 7.5% soybean meal and synthetic lysine. Raw soybeans were added at levels of 8.75, 11.90, 15.05, and 18.20% of the diet. The raw soybean additions replaced the synthetic lysine and part of the milo in the diet and provided lysine levels of .60, .67, .74, and .81% as raw soybean level increased, respectively. Increasing level of raw soybeans had no affect on average daily gain (ADG) or average daily feed intake (ADFI). However, pigs fed increasing levels of raw soybeans had poorer (linear P<.10) feed conversion (F/G). In a second trial, pigs were fed the same control diet or diets containing 3.25% added fat from either raw soybeans, roasted soybeans, or soybean oil. As in the first trial, neither ADG nor ADFI were affected by dietary treatment; however, pigs fed diets containing roasted soybeans or soybean oil had improved F/G compared to pigs fed the control or raw soybean diet. These data indicate that for finishing pigs (> 125 lb) additions of raw soybeans up to 18.2% of the diet did not affect ADG; however, F/G becomes poorer as raw soybean level increases. Furthermore, fat additions from roasted soybeans or soybean oil are utilized more efficiently than that from raw soybeans.
Keywords: Swine; Raw soybeans; Roasted soybeans; Soybean oil; Finishing pigs